Integrasi Nilai Amanah dalam Manajemen dan Perencanaan Pendidikan Islam: Studi Pustaka dan Kerangka Operasional - Mauludi, Sulton Arif (Epistemic: Jurnal Ilmiah Pendidikan, 2026)
This study addresses the limited availability of empirically grounded planning models in the governance of modern Islamic boarding schools (pesantren), where planning practices are often informal, insufficiently participatory, and weakly integrated with implementation and evaluation processes. This study aims to develop a good practice–based planning model to strengthen institutional governance, using a case study of Pondok Pesantren Al Ittihad Cianjur, Indonesia. A qualitative case study approach was employed, supported by in-depth interviews, questionnaires, and institutional document analysis to capture the dynamics of planning practices within the pesantren context. The findings reveal that planning processes characterized by participation, transparency, and continuous evaluation significantly enhance role clarity, organizational coordination, and program effectiveness. Furthermore, the integration of experiential knowledge from previous programs into planning practices enables the development of adaptive and context-sensitive governance mechanisms. This study contributes to Islamic education management literature by offering an empirically grounded and operational planning model that moves beyond normative frameworks. Practically, the model provides actionable guidance for pesantren administrators in designing sustainable and effective planning systems aligned with institutional values and contemporary governance demands.